CLINICAL PECULIARITIES OF EXTERNAL GENITAL ENDOMETRIOSIS - O. N. Loginova; M. M. Sonova (IRBIS LLC, 2016)
we studied the clinical peculiarities of 115 women with external genital endometriosis of different heavy degree (I-IV). Woman with external genital endometriosis suffer from different diseases, they have low healthy index, that is the cause of unfavorable background for development pathological process or disease. Majority of woman with external genital endometriosis suffer from inflammatory process in uterus and tubes that gives additional unfavorable condition for development external genital endometriosis.